Study of the Madden-Julian Oscillation (MJO) Scheme in South Sulawesi Province - Tri Utari; Achmad Yasir Baeda; Chairul Paotonan (Departemen Teknik Sistem Perkapalan, Universitas Hasanuddin, 2022)
The Madden-Julian Oscillation (MJO) is a phenomenon of the propagation of oscillatory waves that move eastward to the earth with a repetition time of 30-90 days and the impact is very strongly felt in low-latitude areas, near the equator and occurs for the first time in the Indian Ocean and moves eastward between 100 latitude and 100 latitude. MJO is closely related to an increase in excessive rainfall during the rainy season and even the dry season in Indonesia. This research was conducted with the aim of analyzing the effect of the rainfall parameter on MJO and the scheme for the emergence of MJO in South Sulawesi Province, through empirical methods with statistical calculations, based on MJO data in the form of MJO amplitude index values and daily rainfall data for South Sulawesi Province. MJO data was taken from BoM while rainfall data was obtained from NASA TRMM 3B42RT with a time range from 2010 to 2019. Both data were filtered for MJO focusing on phases 2 and 3 (Indian Ocean) and 4 and 5 (Indonesian Maritime Continent) and then analyzed the correlation with sensitivity analysis by simple linear regression, and data plotted on a graph for each year. South Sulawesi Province is one in Indonesia which is located in the southern part of Sulawesi Island. Astronomically, South Sulawesi is located at 0°12' - 8° South Latitude and 116°48' - 122°36' East Longitude. Its geographical location is in the middle of the Indonesian Maritime Continent (BMI), there is a strong positive dominant correlation effect in the province of South Sulawesi with an r of 0.712. This means that the rainfall parameter in South Sulawesi Province can have a strengthening influence on the MJO. Based on the graphical scheme of the emergence of MJO in the province of South Sulawesi, there was an increase in rainfall during phases 4 and 5 which occurred for eight days. In addition, the influence of ENSO and IOD can strengthen MJO or even trigger MJO and still cause excessive rainfall which is influenced by these global factors, besides that local factors also affect rainfall such as monsoon winds and topographical conditions that are different in each province. So not all of the rainfall that occurs is caused by MJO activity.